The Use of Botulinum Toxin in Flap Surgery: A Review of the Literature. (August 2019) - Segreto, Francesco; Marangi, Giovanni Francesco; Signoretti, Matteo; Cazzato, Vito; Giorgino, Riccardo; Alessandri-Bonetti, Mario; Persichetti, Paolo
Botulinum neurotoxin-A and botulinum neurotoxin-B have been shown to play a potential role in improving flap survival in animal models. The aim of this study is to review indications as well as to study injection timing, technique, and doses of botulinum neurotoxin-A and botulinum neurotoxin-B in animal models. Seventeen articles describe a total of 266 animals that underwent botulinum toxin injections before or during flap harvesting or vascular anastomosis procedure. All the studies demonstrated a beneficial effect of botulinum toxin administration in flap surgery or vascular anastomosis. Botulinum neurotoxin-A injection was shown to be a reliable approach in reducing vascular complications rate and increasing survival of flaps in animal models. The main conclusions drawn from the study include the following: perivascular injections targeting each vascular pedicle are preferred in cases of free flaps or axial flaps; subdermal injections are favorable in cases of random pattern skin flaps; and injections should be performed 7 days before flap elevation.